Links between intuitive and mindful eating and mood: do food intake and exercise mediate this association? - Açik, Murat; Aslan Çin, Nazlı Nur (Frontiers Media SA, 2025)
Background: In recent years, intuitive eating (IE) and mindful eating (ME) have emerged as promising approaches for developing a healthier relationship with food. Research also suggests that diet can significantly impact one's mental health. Nevertheless, there is no evidence to suggest that IE or ME can be associated with mental wellbeing through the influence of dietary patterns or practices. This study investigates the influence of IE and ME on mental wellbeing by affecting dietary practices. Methods: In this cross-sectional study, 990 adults were administered the intuitive eating scale-2 (IES-2), the mindful eating questionnaire (MEQ), and the Food Mood Questionnaire (FMQ). Briefly, FMQ consists of weekly servings of food groups known to influence brain function and chemistry and the Kessler psychological distress scale (K-6). Correlation analyses were performed to determine the relationships among K-6, IES-2, MEQ, and food groups, and path analyses were performed to assess the mediating effects of food groups on the relationship between the K-6 scale, IES-2, and MEQ. Results: A moderate negative association was found between the K-6 scale and IES-2 and MEQ (r = ?0.47 and ?0.36, respectively). Furthermore, exercise, breakfast, dairy products, fruits, and dark green leafy vegetables (DGLV) were directly related to psychological distress (path coefficient = ?0.104, ?0.151, ?0.181, ?0.235, and ?0.238, respectively), while IES-2 and MEQ had indirect associations with psychological distress via FMQ components (path coefficient = ?0.262 and ?0.212). Among the IES-2 sub-dimensions, Unconditional Permission to Eat (UPE) and Reliance on Hunger and Satiety Cues (RHSC) were found to be indirectly associated with psychological distress through mediatory effects of exercise, breakfast, dairy, fruit, and DGLV. Breakfast and DGLV also mediated partially indirect negative effects of recognition (a sub-dimension of MEQ) on the K-6 scale. Conclusion: This study showed that adopting IE and ME habits effectively associated dietary and lifestyle practices and that some dietary practices and exercise were important for the link between IE and ME to mental distress. Copyright © 2025 Açik and Aslan Çin.
Keywords: dietary patterns; exercise; intuitive eating; mindful eating; psychological distress